2014
DOI: 10.21776/ub.apmba.2014.003.02.3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Local Culture on Financial Performance in Property Firms in Bali

Abstract: The research studies local culture reflected through pray, hard work, honesty, tatwamasi and gotong royong influencing property sales and company assets. Fifty companies are qualified as sample of sixty one property companies actively operated in 2013. Data is collected through questionnaire having tested for its reliability and validity before distributed to those fifty companies. The collected data is analyzed with multiple regression. Result shows that hard work, honesty, tatwamasi and gotong royong culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
2
14
1
Order By: Relevance
“…The closeness to God reflected in the attitude that puts the LPD managers' harmonization in providing credit services. Sincere service without imposed will encourage closeness to customers and the added confidence that if we do good will obtain good results (karmapala) Astawa and Sudika (2014). Through sincere service raises heart closeness between customers with LPD that will encourage honesty to occupy all the agreements made so that the performance can be increased (Yaron et al, 1997;.…”
Section: Practical Harmonious Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The closeness to God reflected in the attitude that puts the LPD managers' harmonization in providing credit services. Sincere service without imposed will encourage closeness to customers and the added confidence that if we do good will obtain good results (karmapala) Astawa and Sudika (2014). Through sincere service raises heart closeness between customers with LPD that will encourage honesty to occupy all the agreements made so that the performance can be increased (Yaron et al, 1997;.…”
Section: Practical Harmonious Culturementioning
confidence: 99%
“…The concept of harmonious relationship with environments provides benefit to the value of the company and supports the government's green program. This concept is already a famous Balinese culture with compassion Olas (Astawa and Sudika, 2014) meaning that damage the environment means damage to the company, thus safeguarding the environment is a must.…”
Section: Practical Harmonious Culturementioning
confidence: 99%
See 1 more Smart Citation
“…One of the organizational cultures that come from the local culture is the harmony culture called tri hita karana culture which is run on the business of tourism (Astawa et al, 2018& Surya et al, 2017. This culture is acknowledged by the World Tourism Organization (WTO) in conducting Tourism business in Indonesia and as an organizational culture (Astawa et al, 2018;Surya et al, 2017;Shahzad et al2017;Astawa & Sudika, 2014;Saputra, 2012) . A culture of harmony is universal which promotes harmonization of God, man, and nature.…”
Section: Introductionmentioning
confidence: 99%
“…Harmonious culture develops into an organizational culture based on several types of research by Astawa, (2013); Astawa and Sudika, (2014);PutuAstawa et al (2016) that found that harmonious culture called tri hita karana (THK) had a significant influence on the improvement of the company's performance and it was implemented well in Bali. The culture has an important role in decreasing the credit risk level in village credit institution (Astawa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%